Pengaruh Pengoperasian Reaktor Kartini terhadapKadar DO, BOD, dan COD Air Pendingin primer - Agus Budhie Wijatna (Forum Teknik, 2004)
Affiliation—Country—Bio Statement Principal contact for editorial correspondence. NameTri Wulan Tjiptono Affiliation—Country—Bio StatementPusat Penelitian dan  Pengembangan  Teknologi  Maju  -  BATAN, Yogyakarta NameTony Dwi Susanto Affiliation—Country—Bio StatementFakultas Teknik Industri,  UPN Veteran, YogyakartaTitle and AbstractTitle  AbstractIn  light  water  reaclor  (LWR) systems,  water coolant passes through  reactor  core  to  remove heat  generated  by fission processes.  Therefore,  the  temperature  of water  coolant raise  and thewater  coolant  is  irradialed  by neutrons from reactor core.The research was  directed  to  explorethe influences  of  both of them  to  the  contents of Dissolved  Oxygen  (DO), Biological OrygenDentand  (BOD)  and  Chemical  Oxygen Demand  (COD).The  research  wss done by  chemical titration method  to  measure  the  content  of DO,  BOD5,and COD in the  water  coolant  in  which  the reactor  was  operated  at   critical  condition  andconstant  power.  water  samplingwere   done  after  45',90',  l3s',  IB0',225',  and  270',   reactoroperation.The results  of  this  research  are:  (1)  the  temperature  of the  coolant  is  increasing  asoperating  time function, (2) the content  of DO is  also  increasing,  while  BOD5 and  COD tends  tobe constant,  and  (3)in  general  the reactor  water coolant  is  safe  to  be released  to the environment.Keywords:  water coolant,  heat,  irradiation, chemical titration, DO